A Review of the some aspects for the development of ZnO based photocatalysts for a variety of applications - Baibara, O.E.; Radchenko, M.V.; Karpyna, V.A.; Ievtushenko, A.I. (Physics and Chemistry of Solid State, 2021)
Today, one of the most important problems for humanity is the pollution of the environment with various organic compounds that worsen the health of the peoples. The most dangerous pollutants are complex compounds that do not degrade under natural conditions. One way to solve the problem of pollution is to use photocatalysis to degrade harmful compounds. Zinc oxide nanostructures exhibit attractive photocatalytic and antibacterial properties due to the increased reactivity of the nanoparticle surface, which allows the efficient decomposition of organic pollutants. In this review, various methods for enhancing the photoefficiency of ZnO nanostructures are considered. It is shown that ZnO nanoparticles with specific surfaces (spherical, nanowires, nanoflowers), which are characterized by a high surface area, have a high removal rate of various pollutants. Such methods of improving the photocatalytic properties of ZnO as the band gap engineering, doping with metal/nonmetal, the combination of ZnO with other materials, formation of hybrid structures are considered.